Scleractinian coral recruitment density in coastal water of Balok, Pahang, Malaysia - Rani, Mohd Husaini; Saad, Shahbudin; Khodzori, Mohd Fikri Akmal; Ramli, Rafindde; Yusof, Muhamad Hamizan (Universiti Teknologi Malaysia, 2015)
Study on scleractinian coral recruitment is important in understanding the mechanisms that regulate their population and the resilience of coral reef communities to disturbance. This study aims to investigate temporal recruitment density of scleractinian coral at selected remote area in Balok, Pahang. Two types of settlement plates, which are terra-cotta tiles and artificial reef, were deployed at three stations to determine the recruitment density. The retrieval of the settlement plate was done at every three months interval started from March to September 2014. A total of 159 coral recruits were counted with mean recruitment densities on both terracotta tiles was 1.52 ± 0.65 and artificial reef plate was 4.37 ± 1.84 respectively. Recruitment was dominated by Platygyra (36%) followed by Porites (32%), Fungia (17%), Turbinaria (7%), Acropora (2%), Stylopora (2%), Montipora (1%), Leptoria (1%), Favites (1%) and Echinophyllia (1%). Kruskal - Wallis ANOVA test shown that recruitment densities varied significantly with plate’s orientation (p < 0.05), but not with sampling stations, type of substrates and month retrieval. Artificial reef plate has better recruitment densities compared to terra-cotta tiles. Coral spat settlement and recruitment patterns were consistent with adult coral distributions. The percentage cover of adult coral varied within the three stations. A total of 33 coral genera from 13 families were recorded during coral video transect survey with Station 3 showed the highest H’ (2.35). Meanwhile, Station 2 showed higher EH’ indexes with 0.82. Therefore, results of this study is important because coral recruitment pattern reflect its adult coral population, and if it closely monitored and harvested sustainably, the survival of parent population could be increased for successful breeding.